Genetic diversity, population structure and differentiation of rice species from Niger and their potential for rice genetic resources conservation and enhancement - (:unkn) unknown (My University, 2014)
Rice genetic resources conservation and evaluation is crucial to ensure germplasm sources for further crop breeding. We conducted a wide collection of Oryza species in Niger and characterize its diversity with microsatellites (or simple sequence repeats, SSR). The aims of this research were to get a better understanding of the extent of genetic diversity, its structure and partition within rice eco-geographical zones of Niger. There were 264 accessions found in farmers’ and other fields: 173 O. sativa (Asia’s rice), 65 O. glaberrima (Africa’s rice), 25 O. barthii, and 1 O. longistaminata (weedy perennial rice), which were genotyped with 18 SSR. A total of 178 alleles were detected, with a mean of 9.89 alleles per locus. The polymorphism information content was 0.65 and heterozygosity was estimated as 0.14. Two main well-differentiate genotypic groups, which correspond to Asian and African rice species, were identified. The SSR set divided the Asia’s rice group (solely indica) into irrigated and floating rice, with rainfed lowland rice in between. The African rice species group was composed of O. glaberrima, O. longistaminata and O. barthii accessions, but without any clear genetic differentiation among them likely due admixtures within the samples of O. barthii. Five accessions that could be natural interspecific hybrids were too admixed for assigning them to any of the two well-differentiated groups. The partitioning of the overall diversity showed that maximum variation was within genotypic groups and subgroups or cropping ecologies, rather than between eco-geographical zones. The eco-geographical distribution of the diversity suggests germplasm exchange in Niger. Next-steps for conserving rice and crop wild relatives in Niger could be taken using the findings of this research.
Keywords: African Research